2014
DOI: 10.1371/journal.pntd.0002604
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Vaccine Potential of Plasmid DNA Encoding Nine Mycolactone Polyketide Synthase Domains in Mycobacterium ulcerans Infected Mice

Abstract: There is no effective vaccine against Buruli ulcer. In experimental footpad infection of C57BL/6 mice with M. ulcerans, a prime-boost vaccination protocol using plasmid DNA encoding mycolyltransferase Ag85A of M. ulcerans and a homologous protein boost has shown significant, albeit transient protection, comparable to the one induced by M. bovis BCG. The mycolactone toxin is an obvious candidate for a vaccine, but by virtue of its chemical structure, this toxin is not immunogenic in itself. However, antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Mycolactone is the key virulence factor produced by M. ulcerans and an attractive vaccine target, but the molecule is poorly immunogenic (55). However, the PKS enzymes used by the bacterium to synthesize mycolactones – are highly conserved and immunogenic (49, 56-58). Therefore, we hypothesized that targeting the conserved enzymatic domains of the mycolactone PKS could be an effective vaccine strategy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mycolactone is the key virulence factor produced by M. ulcerans and an attractive vaccine target, but the molecule is poorly immunogenic (55). However, the PKS enzymes used by the bacterium to synthesize mycolactones – are highly conserved and immunogenic (49, 56-58). Therefore, we hypothesized that targeting the conserved enzymatic domains of the mycolactone PKS could be an effective vaccine strategy.…”
Section: Resultsmentioning
confidence: 99%
“…One domain in particular, the enoyl reductase (ER) protein domain, elicits serum antibodies in BU patients and healthy controls in BU endemic regions (57). The ER protein expressed as an antigen in a DNA-protein prime-boost vaccine has also been shown to reduce bacterial burden in a mouse footpad M. ulcerans challenge model (49). Here, we utilised the ER protein to create a novel BU vaccine candidate by electrostatically associating it with the TLR-2 agonist-based lipopeptide R 4 Pam 2 Cys.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether in the form of a plasmid DNA vaccine or as a recombinant protein, vaccination strategies with Ag85A conferred some degree of protection by eliciting a cellular response with high levels of IFN-γ, IL-2 and Ag85-specific IgGs, but, similarly to BCG, eventually failed to deter disease development [163][164][165][166]. Likewise, a vaccine employing DNA plasmids of polyketide synthase domains of Mycobacterium leprae Hsp65, previously tested in a murine model of tuberculosis, conferred protection against BU only for a few months, despite the high homology of the amino acid sequence with the M. ulcerans orthologue [167,168]. Therefore, better targets for immunization are still to be found and, to this end, a comparative genomics screening study identified several essential components of M. ulcerans that could provide important hints to direct future vaccination strategies [169].…”
Section: (Un)successful Preventive Approachesmentioning
confidence: 99%
“…Priming with a DNA-based vaccine encoding multiple MU polyketide synthase modules and boosting with recombinant protein by Roupie et al . yielded differential levels of antigen-specific IgG responses, as well as IFNγ and IL-2 secretion upon recombinant MU antigen stimulation [12]. However, no improvement in protection over the level conferred by BCG vaccination was observed.…”
Section: Introductionmentioning
confidence: 99%